Potensi Curug Cinulang Sebagai Wisata Berkelanjutan di Kabupaten Bandung - Dandi Maulana Faizulhaq; Dally Nur Arif; Dias Pratami Putri (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
His research uses qualitative research methods to determine the potential of Curug Cinulang as a sustainable tourist destination in Bandung Regency. By using the triple bottom line concept which includes economic, environmental and social aspects, this research examines how tourism management at Curug Cinulang can provide balanced benefits for the surrounding community, the natural environment and the local economy. Data was obtained through in-depth interviews with various stakeholders, field observations, and document analysis. The results of the research show that management involving the active participation of local communities not only improves economic welfare through the creation of jobs and business opportunities, but also encourages the preservation of the natural environment around water. plunge. In addition, community involvement in tourism management creates a sense of shared ownership and responsibility, thereby strengthening social cohesion. These results show that Curug Cinulanghas great potential to develop sustainable tourism that provides long-term benefits for all stakeholders..